Juror Decision Making in Acquaintance and Marital Rape: The Influence of Clothing, Alcohol, and Preexisting Stereotypical Attitudes. Issue 5 (March 2021) - Osborn, Kirsty; Davis, Josh P.; Button, Susan; Foster, John
Stereotypical biases about women's roles in intimate relationships including their marital status and lifestyle choices such as clothing and alcohol use influence juror attributions of rape case defendant guilt, potentially reducing access to justice for victims. Across two mock-juror decision-making experiments, participants read identical fictitious sexual assault vignettes varying in intoxicated defendant–complainant relationship (married vs. acquaintance), accompanied by photographs of complainant clothing at the crime (body revealing vs. plain) and in court (smart vs. casual). Experiment 2 additionally described the defendant's alcohol consumption as either under or over the drink drive limit. Most participants delivered guilty verdicts (Experiment 1: 86.7%; Experiment 2: 75.5%), recommending mean prison sentences of 5.04 years in Experiment 1 ( n = 218 students) and 4.33 years in Experiment 2 ( n = 1, 086 members of public). In Experiment 1, guilty verdict rates and sentences were significantly higher when the married—but not the acquaintance—complainant dressed smartly rather than casually in court. In Experiment 2, significantly more guilty verdicts were delivered by females (80.3%) than males (66.9%), while sentence lengths were longer in acquaintance ( M = 4.52 years) than married conditions ( M = 4.10). Significant interactions between defendant alcohol use and clothing choice of the married—but not the acquaintance complainant—at the crime also influenced sentencing decisions. Higher scores on additionally administered scales measuring rape myth acceptance and sexist attitudes, but not alcohol expectancies, predicted lenient sentencing decisions in both experiments. These findings highlight how "rape myths" concerning marriages drive juror decisions. Prosecuting lawyers should use these results to better challenge these attitudes in court. Internationally, rape is often unreported to the police, and married victims may be more willing to come forward if they believe unbiased access to justice is likely.